2023
DOI: 10.1002/ski2.225
|View full text |Cite
|
Sign up to set email alerts
|

Using electrocardiogram electrodes to monitor skin impedance spectroscopic response when skin is subjected to sustained static pressure

Abstract: Background Impedance spectroscopy is a non‐invasive technique which can be used to monitor skin barrier function, with potential applications in early‐stage pressure ulcer detection. This paper describes how changes in skin impedance, due to mechanical damage of the stratum corneum by tape stripping or applied pressure, can be straightforwardly measured using commercial electrocardiogram electrodes and a relatively low‐cost impedance analyser. Two models of pressure injury were studied, an ex vivo porcine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…The stratum corneum is composed of several layers of highly resistive dead cells; the reduction in resistance indicates that the skin barrier function was compromised by urease activity. 38 , 41 No trend was reported in the stratum corneum moisture and TEWL data (Figure S1), suggesting that the instruments were less sensitive to the experimental conditions compared to impedance spectroscopy. Further studies on P. mirabilis showed a time‐dependency for skin damage; 10 6 CFU/ml causes significant damage after 8–10 h whilst 10 9 CFU/ml requires 2 h (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The stratum corneum is composed of several layers of highly resistive dead cells; the reduction in resistance indicates that the skin barrier function was compromised by urease activity. 38 , 41 No trend was reported in the stratum corneum moisture and TEWL data (Figure S1), suggesting that the instruments were less sensitive to the experimental conditions compared to impedance spectroscopy. Further studies on P. mirabilis showed a time‐dependency for skin damage; 10 6 CFU/ml causes significant damage after 8–10 h whilst 10 9 CFU/ml requires 2 h (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…These measurements showed that the measured resistance is primarily derived from the skin's stratum corneum. 38 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations